2005
DOI: 10.1210/en.2004-1111
|View full text |Cite
|
Sign up to set email alerts
|

Bipotential Effects of Estrogen on Growth Hormone Synthesis and Storagein Vitro

Abstract: Increased pulses of serum GH coincide with rising estrogens during the reproductive cycle, suggesting estrogen regulation. However, there is lack of agreement about estrogen's direct effects on the pituitary. Pituitaries from cycling female rats were dispersed and plated for 24 h in defined media containing vehicle or 0.001-250 nm 17beta-estradiol. Estrogen (0.01-10 nm) increased the percentages of GH antigen-bearing cells in the anterior pituitary significantly (1.3- to 1.6-fold) and 0.01-1 nm concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
48
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 41 publications
3
48
0
Order By: Relevance
“…Studies in women have shown a concomitant rise in serum E 2 concentration and in GH secretion, in the late follicular phase of the normal menstrual cycle (Faria et al, 1992;Ovesen et al, 1998). Similar results were also obtained in sheep (Landefeld and Suttie, 1989;Malven et al, 1995;Scanlan and Skinner, 2002), mice (Yan et al, 2004) and rats (Childs et al, 2005). In a study, female rat pituitary cells were cultured for 24 h in defined media containing vehicle or E 2 in different concentrations.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Studies in women have shown a concomitant rise in serum E 2 concentration and in GH secretion, in the late follicular phase of the normal menstrual cycle (Faria et al, 1992;Ovesen et al, 1998). Similar results were also obtained in sheep (Landefeld and Suttie, 1989;Malven et al, 1995;Scanlan and Skinner, 2002), mice (Yan et al, 2004) and rats (Childs et al, 2005). In a study, female rat pituitary cells were cultured for 24 h in defined media containing vehicle or E 2 in different concentrations.…”
Section: Discussionsupporting
confidence: 56%
“…In a study, female rat pituitary cells were cultured for 24 h in defined media containing vehicle or E 2 in different concentrations. Addition of lowdose (0.01 to 1 nM or 0.01 to 10 nM) E 2 increased the percentage of GH mRNA-bearing cells, whereas high dose of E 2 (100 to 250 nM) either had no effect or inhibitory effects on the percentage of GH mRNA-bearing cells (Childs et al, 2005). Therefore, E 2 dose dependently increases GH secretion.…”
Section: Discussionmentioning
confidence: 91%
“…Our studies sought to address these questions with new dual labeling techniques that identified both receptor activity and hormone activity in pituitary cells (Childs, 2002;Childs et al, 2004). We also designed the estrogen treatment paradigm to include a broad range of concentrations.…”
mentioning
confidence: 99%
“…We also designed the estrogen treatment paradigm to include a broad range of concentrations. to test the hypothesis that estrogen's actions might be bipotential (Childs et al, 2004)..We hypothesized that the controversy in the literature might be related to the concentration of estrogen used in the previous studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation